2011
DOI: 10.1111/j.1365-2958.2011.07597.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel two‐gene requirement for the octanoyltransfer reaction of Bacillus subtilis lipoic acid biosynthesis

Abstract: SUMMARY The Bacillus subtilis genome encodes three apparent lipoyl ligase homologues: yhfJ, yqhM, and ywfL which we have renamed lplJ, lipM and lipL, respectively. We show that LplJ encodes the sole lipoyl ligase of this bacterium. Physiological and biochemical characterization of a ΔlipM strain showed that LipM is absolutely required for the endogenous lipoylation of all lipoate-dependent proteins, confirming its role as the B. subtilis octanoyltransferase. However, we also report that in contrast to E. coli,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
123
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(129 citation statements)
references
References 35 publications
6
123
0
Order By: Relevance
“…Complementation was tested on M9 minimal agar plates with glycerol as the sole carbon source to avoid bypass of succinate-and acetate-dependent growth by fermentative metabolism (33). Due to the E. coli QC146 ⌬lplA mutation, the strain is unable to grow with lipoic acid supplementation; however, growth proceeds robustly when a plasmid encoding lipoate ligase activity is present (5,10,13). Upon expression of the putative S. coelicolor lplA-expressing gene, the E. coli strain grew well, but only when the medium contained lipoic acid (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complementation was tested on M9 minimal agar plates with glycerol as the sole carbon source to avoid bypass of succinate-and acetate-dependent growth by fermentative metabolism (33). Due to the E. coli QC146 ⌬lplA mutation, the strain is unable to grow with lipoic acid supplementation; however, growth proceeds robustly when a plasmid encoding lipoate ligase activity is present (5,10,13). Upon expression of the putative S. coelicolor lplA-expressing gene, the E. coli strain grew well, but only when the medium contained lipoic acid (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the function and protein structure of the E. coli LplA lipoate ligase are well established (4,5,7,11), the presence of this activity in other bacteria has been demonstrated only in B. subtilis, in which the ligase is called LplJ (10), and in Listeria monocytogenes, a bacterium related to B. subtilis that is auxotrophic for lipoic acid and that encodes two ligases, both of which function in lipoic acid scavenging (12). Like B. subtilis, Streptomyces coelicolor is a Gram-positive soil bacterium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical assays showed that the LipM protein had no ligase activity and instead catalyzed octanoyl transfer from octanoyl-ACP (87). Another of the putative ligase genes (now called LplJ) was shown to encode a protein that functionally replaced LplA in E. coli and had only ligase activity (118). However, the protein (called LipL) encoded by the third putative lipoate ligase gene had no octanoyltransferase or ligase activity.…”
Section: Involvement Of the Glycine Cleavage H Protein In 2-oxoacid Dmentioning
confidence: 99%
“…First, B. subtilis strains lacking the LplJ ligase should show a growth defect only in strains that also lack LipA. This was the case (118). Second, strains lacking the LipM octanoyltransferase or the LipL amidotransferase should require lipoic acid for growth in the absence of the products of the 2-oxoacid dehydrogenases.…”
Section: Involvement Of the Glycine Cleavage H Protein In 2-oxoacid Dmentioning
confidence: 99%